2014
DOI: 10.1096/fj.14-250332
|View full text |Cite
|
Sign up to set email alerts
|

SAA drives proinflammatory heterotypic macrophage differentiation in the lungviaCSF‐1R‐dependent signaling

Abstract: Serum amyloid A (SAA) is expressed locally in chronic inflammatory conditions such as chronic obstructive pulmonary disease (COPD), where macrophages that do not accord with the classic M1/M2 paradigm also accumulate. In this study, the role of SAA in regulating macrophage differentiation was investigated in vitro using human blood monocytes from healthy subjects and patients with COPD and in vivo using an airway SAA challenge model in BALB/c mice. Differentiation of human monocytes with SAA stimulated the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Our data also suggest that IL-1β may function in a cell autonomous manner in fetal lung macrophages to accelerate the maturation process. Recent studies have reported similar mechanisms linking inflammatory mediators with macrophage differentiation in the lung (45, 46). In addition to cytokine effects on resident macrophages, recruitment of fetal monocytes into the developing lung may also lead to changes in lung innate immunity.…”
Section: Discussionmentioning
confidence: 66%
“…Our data also suggest that IL-1β may function in a cell autonomous manner in fetal lung macrophages to accelerate the maturation process. Recent studies have reported similar mechanisms linking inflammatory mediators with macrophage differentiation in the lung (45, 46). In addition to cytokine effects on resident macrophages, recruitment of fetal monocytes into the developing lung may also lead to changes in lung innate immunity.…”
Section: Discussionmentioning
confidence: 66%
“…Ly6C pos macrophages entering the injured muscle highly expressed genes involved in inflammation, including acute-phase proteins, such as SAA3, S100A8/9, Lipocalin-2, and Haptoglobin (32). Both pathogen-associated and damageassociated molecular pattern molecules induce macrophage expression of S100A8 and S100A9 (33), which dimerize to form calprotectin, which, in turn, triggers SAA3 expression (34) by macrophages (35)(36)(37). Interestingly, macrophage-derived calprotectin is an early contributor of skeletal muscle myositis, which is characterized by a huge inflammatory infiltrate (38) and is also upregulated after exercise (39), suggesting that these macrophagederived proteins are crucial for launching the regeneration/remodeling process in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…SAA is a potent chemotactic factor that mediates migration of leukocytes [14] and can also promote expression of proinflammatory mediators under in vitro [25] and in vivo conditions [12]. We have previously shown that SAA induces a proinflammatory macrophage phenotype [26] that stimulated acute neutrophilic lung inflammation in an Fpr2-dependent manner [16].…”
Section: Discussionmentioning
confidence: 99%
“…SAA is also a functional agonist for the formyl peptide receptor 2/lipoxin A 4 (LXA 4 ) receptor (Fpr2/ALX) where it stimulates leukocyte chemotaxis [14]. Furthermore, we have recently shown that local lung challenge with recombinant SAA potently stimulates neutrophilic inflammation via IL-17A-dependent mechanisms [15,16]. SAA can also promote neutrophil survival by suppressing the apoptotic machinery through activation of ERK and PI3K/Akt signaling pathways [17].…”
Section: Introductionmentioning
confidence: 99%